Attenuated Organomagnesium Activation of White Phosphorus1. (26th May 2015) - Arrowsmith, Merle; Hill, Michael S.; Johnson, Andrew L.; Kociok‐Köhn, Gabriele; Mahon, Mary F.
Abstract Sequential reactions between a 2, 6‐diisopropylphenyl‐substituted β‐diketiminato magnesium n‐butyl derivative and P4 allow the highly discriminating synthesis of unusual [nBu2P4]2− and [nBu2P8]2− cluster dianions.